2021
DOI: 10.1111/dth.14702
|View full text |Cite
|
Sign up to set email alerts
|

How to assess patient satisfaction regarding physician interaction: A systematic review

Abstract: Patient satisfaction is an important health care quality indicator. This is particularly relevant in chronic diseases, such as, many dermatological diseases. The purpose of the current systematic review was to assess the validated tools measuring patient satisfaction with physician interaction. We performed a systematic review search in Pubmed, Cochrane Library, and EMBASE. The psychometric properties of the instruments and the domains explored were assessed. Overall, 2229 articles were extracted from the lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Having control of their disease is also central to the QoL and well-being of people with psoriasis, and this can be achieved by ensuring that they have access to comprehensive information on the available treatments and by building a relationship of mutual trust and respect between the individual with psoriasis and their HCP. 21 Finally, the overarching consensus statement helps us to understand that the concept of 'freedom of disease' is multifaceted, with all five themes needing to be addressed to allow the individual with psoriasis to feel that they have fully reached this state. Although not specifically addressed in this consensus statement, 'freedom from disease' in psoriasis also implies freedom from any potential comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Having control of their disease is also central to the QoL and well-being of people with psoriasis, and this can be achieved by ensuring that they have access to comprehensive information on the available treatments and by building a relationship of mutual trust and respect between the individual with psoriasis and their HCP. 21 Finally, the overarching consensus statement helps us to understand that the concept of 'freedom of disease' is multifaceted, with all five themes needing to be addressed to allow the individual with psoriasis to feel that they have fully reached this state. Although not specifically addressed in this consensus statement, 'freedom from disease' in psoriasis also implies freedom from any potential comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…As with most jobs, but particularly with contingent work that involves working with multiple clients during a shift (ie, gigs), time availability is a recurring issue raised by employees 49–51 . Time was a critical factor related to implementing self-care practices across all MTs, both as a facilitator and barrier.…”
Section: Discussionmentioning
confidence: 99%
“…11,21,40,41,47,48 As with most jobs, but particularly with contingent work that involves working with multiple clients during a shift (ie, gigs), time availability is a recurring issue raised by employees. [49][50][51] Time was a critical factor related to implementing self-care practices across all MTs, both as a facilitator and barrier. Based on the regression models, when time was a facilitator, it was associated with implementing an average of 2.1 more self-care practices; in contrast, when time was identified as a barrier it was associated with implementing 0.9 fewer self-care items despite wanting to make these changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several tools have been designed to assess patient satisfaction with health care: A recent systematic review evaluated 13 such tools [ 14 ] and concluded that the EUROPEP tool [ 15 ] has been the most internationally validated of them and thus is suitable for use in international settings. In addition, the tool has been successfully used to compare patient satisfaction with health care during the pre- and post-economic crisis periods in Greece, which documents its sensitivity in showing the dynamics of satisfaction in that time and creates grounds for its application to compare patient satisfaction with care in the pre-COVID-19 period and during the COVID-19 pandemic [ 16 ].…”
Section: Introductionmentioning
confidence: 99%